Hypertonic Saline Suppresses NADPH Oxidase-Dependent Neutrophil Extracellular Trap Formation and Promotes Apoptosis - Nadesalingam, Ajantha; Chen, Jacky H. K.; Farahvash, Armin; Khan, Meraj A. (Frontiers in Immunology, 2018)
Tonicity of saline (NaCl) is important in regulating cellular functions and homeostasis. Hypertonic saline is administered to treat many inflammatory diseases, including cystic fibrosis (CF). Excess neutrophil extracellular traps (NETs) formation, or NETosis, is associated with many pathological conditions including chronic inflammation. Despite the known therapeutic benefits of hypertonic saline, its underlying mechanisms are not clearly understood. Therefore, we aimed to elucidate the effects of hypertonic saline in modulating NETosis. For this purpose, we purified human neutrophils and induced NETosis using agonists diacylglycerol mimetic phorbol myristate acetate (PMA), Gram-negative bacterial cell wall component lipopolysaccharide (LPS), calcium ionophores (A23187 and ionomycin from Streptomyces conglobatus), and bacteria (Pseudomonas aeruginosa and Staphylococcus aureus). We then analyzed neutrophils and NETs using Sytox green assay, immunostaining of NET components and apoptosis markers, confocal microscopy, and pH sensing reagents. This study found that hypertonic NaCl suppresses nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX2)-dependent NETosis induced by agonists PMA, Escherichia coli LPS (0111:B4 and O128:B12), and P. aeruginosa. Hypertonic saline also suppresses LPS- and PMA- induced reactive oxygen species (ROS) productionIt was determined that supplementing H2O2 reverses the suppressive effect of hypertonic saline on NOX2-dependent NETosis. Many of the aforementioned suppressive effects were observed in the presence of equimolar concentrations of choline chloride and osmolytes (D-mannitol and D-sorbitol). This suggests that the mechanism by which hypertonic saline suppresses NOX2-dependent NETosis is via neutrophil dehydration. Hypertonic NaCl does not significantly alter the intracellular pH of neutrophils. We found that hypertonic NaCl induces apoptosis while suppressing NOX2-dependent NETosis. In contrast, hypertonic solutions do not suppress NOX2-independent NETosis. Although hypertonic saline partially suppresses ionomycin-induced NETosis, it enhances A23187-induced NETosis, and it does not alter S.aureus-induced NETosis. Overall, this study determined that hypertonic saline suppresses NOX2-dependent NETosis induced by several agonists; in contrast, it has variable effects on neutrophil death induced by NOX2-independent NETosis agonists. These findings are important in understanding the regulation of NETosis and apoptosis in neutrophils.